2017
DOI: 10.1039/c7ra03864j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and gas sensing properties of molybdenum oxide modified tungsten oxide microstructures for ppb-level hydrogen sulphide detection

Abstract: Flower-like MoO3@WO3 composite microstructures with abundant nanosheets were obtained by the hydrothermal and impregnation method and then used for high performance sensing of H2S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The oxidation states of the elements present in α-Mo 0.5 W 0.5 O 3 mixed oxide were obtained by XPS (Figure g–i). The peaks corresponding to Mo 6+ 3d 5/2 and Mo 6+ 3d 3/2 were observed at 233.1 and 236.2 eV. , The energy separation of 3.1 eV is in accordance with the literature . The low-intensity spin doublet corresponding to Mo 5+ was observed at 231.8 and 234.7 eV .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The oxidation states of the elements present in α-Mo 0.5 W 0.5 O 3 mixed oxide were obtained by XPS (Figure g–i). The peaks corresponding to Mo 6+ 3d 5/2 and Mo 6+ 3d 3/2 were observed at 233.1 and 236.2 eV. , The energy separation of 3.1 eV is in accordance with the literature . The low-intensity spin doublet corresponding to Mo 5+ was observed at 231.8 and 234.7 eV .…”
Section: Resultssupporting
confidence: 88%
“…Mesoporous molybdenum oxide (MoO 3 ) and tungsten oxide (WO 3 ) have been studied extensively due to their wide range of applications in catalysis, gas sensors, electrochromic/photochromic devices, and energy storage devices. Thus, the combination of molybdenum and tungsten would open up new avenues with enhanced properties. However, there are only few reports on molybdenum tungsten mixed oxides due to difficulties associated with conventional synthesis methods which are wet impregnation, , sputter deposition, , and electrodeposition. The direct reaction between MoO 3 and WO 3 involves sintering for long periods of time (5 days) .…”
Section: Introductionmentioning
confidence: 99%
“…The resulting chemiresistor was capable of detecting 20 ppb H 2 S with a response time of 2 s and a recovery time of 5 s at 250 °C. 614 The excellent gas sensing performance of the MO 3 -WO 3 samples might be ascribed to the heterojunction structure in which a thicker electron depletion layer forms at the interface between MoO 3 and WO 3 , resulting in larger resistance change compared to the pure WO 3 .…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Hu et al reported on ultra-fast detection time at sub-ppm concentrations of H 2 S by integrating MO 3 -WO 3 composite, synthesized by stirring WO 3 nanosheets with definite amounts of ammonium heptamolybdate tetrahydrate in H 2 O followed by calcination at 500 °C, into a gas sensor. The resulting chemiresistor was capable of detecting 20 ppb H 2 S with a response time of 2 s and a recovery time of 5 s at 250 °C . The excellent gas sensing performance of the MO 3 -WO 3 samples might be ascribed to the heterojunction structure in which a thicker electron depletion layer forms at the interface between MoO 3 and WO 3 , resulting in larger resistance change compared to the pure WO 3 .…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…In comparison with the one-dimensional α-MoO 3 sensor, the 2D sheet-shaped α-MoO 3 sensor has a relatively large specific surface area, thus exposing a large number of adsorption sites to gas molecules. For this reason, 2D sheet-shaped α-MoO 3 sensors exhibit excellent gas-detecting functions for a great many gases, like NO 2 , NH 3 , H 2 S, H 2 , ethanol, acetone, and trimethylamine . For example, Jiang et al prepared MoO 3 microsheets by thermally oxidizing the MoO 2 nanospheres, and the sensitivity of the MoO 3 microsheet sensor to 100 ppm TEA was 27.1.…”
Section: Introductionmentioning
confidence: 99%